FRI0175 Anti-drug-antibodies but not igg-4 antibodies against tnf blockers influence the activity of anti-tnf drugs in rheumatoid arthritis. (23rd January 2014) - Benucci, M.; Infantino, M.; Manfredi, M.; Olivito, B.; Sarzi-Puttini, P.; Atzeni, F.
Abstract : Background: Anti-TNF drugs have changed the clinical course of rheumatoid arthritis (RA), but the survival rate and the resistance to the therapy showed that about 30% of RA patients fail to respond to these drugs. Objectives: The aim of our study was to evaluate the correlation between the development of anti-drug antibodies and specific IgG-4 antibodies against TNF inhibitors and the resistance to this therapy in RA patients. Methods: The retrospective study involved 130 established RA patients [98 females and 32 males, mean age 56, 7±12, 3 years, disease duration 6, 3±1.2] who fail to respond to conventional DMARDs treated with anti-TNF agents [32 pts with INF, 58 pts. with ETN, 40 pts with ADA] with a baseline DAS28 range between 3.2-5.6. After 6 months of treatment according to DAS28 values the patients were classified in remission for DAS28 <2.6 (R) and having low disease activity (LDA) for DAS28 range between 2.6-3.2 or non responder (NR)>3.2. The patients were tested for serum anti-drugs antibodies (Anti TNF-α Blocker ELISA kit Immundiagnostik AG, Bensheim - Listarfish, Milan, Italy) and IgG4 specific antibodies against TNF- inhibitors (ImmunoCAP® Assay fluoroenzyme immuno assay Kit for ImmunoCAP250, Phadia, Uppsala, Sweden). Results: After a mean of 6 months in IFN group: 15.65% of the patients were in remission (R ), 31.2 % in LDA and 53.12% NRs; in ETN group 22.41% of the patients in R, 41.37% in LDA, 36.20% NRs, in ADA group 30% of the patients in R, 25% in LDA and 45% NRs. In the INF group the anti-drug antibodies were detected in 21. 87% of the patients and specific IgG-4 antibodies in18%, in ETN group the anti-drug antibodies were detected in 10.34% and specific IgG-4 antibodies in 8.67%, in ADA group the anti-drugs antibodies in 25% and specific IgG-4 antibodies in 5%. The presence of anti-drug antibodies in INF e ADA group correlate with the high percentage of NRs (R:0.032 ;R:0.039). No correlation with the specific IgG-4 antibodies against TNF and clinical response was observed. Conclusions: In patients with RA the presence of all anti-drug antibodies but not the specific IgG-4 antibodies against TNF could influence the activity of TNFblockers in particular in INF and ADA group. This study also confirmed the low immunogenecity of ETN. Disclosure of Interest: None Declared